February friend - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 2009)
Bradley, Brian, Nate, and Lucy follow clues to find whoever left a rabbit in their first-grade classroom on Valentine's Day, because they are worried the rabbit will get sick and die of loneliness.
"A Stepping Stone book."
Keywords: Rabbits -- Fiction; Valentine's Day -- Fiction; Twins -- Fiction; Brothers and sisters -- Fiction; Cousins -- Fiction; Mystery and detective stories